Therapist Behavior During Exposure Tasks Predicts Habituation and Clinical Outcome in Three Randomized Controlled Trials for Pediatric OCD. Issue 3 (May 2021) - Benito, Kristen G.; Machan, Jason; Freeman, Jennifer B.; Garcia, Abbe M.; Walther, Michael; Frank, Hannah; Wellen, Brianna; Stewart, Elyse; Edmunds, Julie; Sapyta, Jeffrey; Franklin, Martin E.
Abstract: This study measured therapist behaviors in relation to subsequent habituation within exposure tasks, and also tested their direct and indirect relationships (via habituation) with clinical outcomes of exposure therapy. We observed 459 videotaped exposure tasks with 111 participants in three clinical trials for pediatric obsessive-compulsive disorder (POTS trials). Within exposure tasks, therapist behaviors and patient fear were coded continuously. Outcomes were habituation and posttreatment change in symptom severity, global improvement, and treatment response. More therapist behaviors that encourage approach—and less use of accommodation, unrelated talk, and externalizing language—predicted greater subsequent habituation during individual exposure tasks (exposure-level), and also predicted improved patient clinical outcomes via higher "total dose" of habituation across treatment (patient-level indirect effect). For six of seven therapist behaviors analyzed, the relationship with subsequent habituation within exposure differed by patient fear (low, moderate, or high) at the time the behavior was used. Two therapist behaviors had direct effects in the opposite direction expected; more unrelated talk and less intensifying were associated with greater patient symptom reduction. Results shed light on the "black box" of in-session exposure activities and point to specific therapist behaviors that may be important for clinical outcomes. These behaviors might be best understood in the context of changing patient fear during exposure tasks. Future studies should test whether therapist behaviors can be experimentally manipulated to produce improvement in clinical outcomes. Highlights: Therapist behaviors relate to clinical outcomes in exposure therapy Therapist behavior should be considered in relation to patient fear during exposure Future studies should determine whether therapist behavior changes patient outcomes